Understanding Physical Activity Patterns Across the School Day in Urban Pre-Kindergarten and Elementary Schoolchildren. Issue 1 (January 2022) - Sacheck, Jennifer M.; Blake, Emily F.; Press, Hannah; Huang, Qiushi; Wright, Catherine M.; Lora, Karina R.; Sylvetsky, Allison C.; Visek, Amanda J.; DiPietro, Loretta
Purpose: Despite recommendations that children accrue ≥60 min/day of moderate-to-vigorous physical activity (MVPA), numerous barriers may exist. We examined school-day MVPA patterns in lower-income children (pre-K to 5th grade) to determine whether they were meeting the minimum school-day guidelines of at least 30-min/day of MVPA and to identify opportunities for intervention. Methods: Students (N = 629, pre-K-5th grade) from 4 urban schools wore Actigraph GT3X+ accelerometers over 2 school days. Mixed effects models evaluated sex- and grade-specific differences in MVPA and sedentary time. Results: Only 34.6% of elementary and 25.3% of pre-K students met the school-time MVPA recommendation. Among elementary-aged children, boys accrued more MVPA than girls (30.8 ± 13.3 vs. 23.5 ± 10.7 min/day; p < 0.0001) with similar sex differences observed among pre-K children (51.3 ± 17.1 vs 41.9 ± 17.5 min/day; p < 0.001). Sedentary time also increased significantly with grade among elementary-aged children (207.9 ± 34.7 vs. 252.0 ± 36.1 min/day for those in 1st and 5th grade, respectively; p < 0.001), with girls accruing more sedentary time than boys (242.5 ± 48.2 vs. 233.8 ± 46.8 min/day; p < 0.0001). Conclusion: MVPA declines across elementary school years, with sex disparities observed as early as pre-K. Extended sedentary bouts and clustering of activity highlight opportunities for more movement throughout the school day.